Regulation Systems State in Connection with Different Psychological Types, Defense Mechanisms and Health Behavior - Lutsenko, O.; Gabelkova, O. (My University, 2016)
In research it was examined state of organism regulation systems by heart rate variability (HRV) analysis. It was hypothesized that various psychological types, defense mechanisms and healthy habits have specific relations with regulation systems. The purpose was to study regulation system state in connection with different psychological types, ego-defense mechanisms and healthy behavior of youth taking into account the gender. It is known that regulation systems disbalance and low HRV bring to decrease of life quality and longevity. At the sample of 217 university students (112 men) were measured HRV indexes, personality types by MMPI, defense mechanisms by Life Style Index and healthy habits by Health Style: A Self Test. It was found that men and women mostly have different correlations between HRV and psychological features. Only two general correlations were revealed: positive connection between lie scale and stress index (SI of HRV) and negative connection between psychological defense mechanism “projection” and sympathetic regulation. We conclude that men’s and women’s psychological features are differently connected with regulation systems. It can be explained by different adaptation strategies of men and women which were designed during evolution time. This fact should be taken into account at designing interventions for changing non-healthy behavior.
Keywords: psychology; psychophysiology; HRV; health